Development of canned pork and peanuts in tomato sauce - Ley, Teldy Sy
The formulation and thermal process were developed for canned pork and peanuts in tomato sauce. The study was divided into three phases. In Phase I, the formulation and descriptive evaluation sheet for the product were developed. A Filipino type of tomato sauce was the most acceptable formulation. The thermal process for the canned product was established in Phase II. A process schedule of the 45 minutes at 250°F was necessary to produce a commercially sterile product. The lethality of the process was calculated using the Graphical and Patashnik meter methods. Results of sensory evaluation revealed that the sauce was orange, slightly thick, and slightly spicy. It had a sweet-sour blend that was just right; and had a "peanut flavor with slight tomato flavor". The product was rated "like very much". In Phase III, the process was verified in a bench scale production. It was found that a longer processing time of 47 minutes was necessary to produce a commercially sterile product. Microbiological, physico-chemical and sensory characteristics of the canned product confirmed that the process applied was adequate. In addition, product was highly acceptable to the panelists.